Great Britain and European integration - Balog Edit; Simon Péter (2004)
My thesis intends to present the relationship between Great Britain and the countries that participated in European integration from the beginning of the 20th century until Margaret Thatcher's fall in 1990. I will prove that Britain behaved as a reluctant European by hesitating to be involved in the process of European integration. This reluctance was expressed to the greatest extent during Margaret Thatcher's years in office. The reasons for the divergence are to be found in the opposing views represented by Great Britain and the Community. In order to show this I am going to use books both about the history of the European unifying process and about Margaret Thatcher's governing periods. Furthermore, the Bruges speech held by the British Prime Minister will serve as evidence.
Keywords: Pedagógusképzés